MANAGING INFORMATION FLOWS IN PHARMACY CHAINS BASED ON LOGISTICS PRINCIPLES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
In the context of digital transformation and increasing competition in the pharmaceutical market, effective management of information flows has become a key factor in improving the performance of pharmacy chains. Fragmentation of data, lack of integration between operational units, and inefficient inventory and order management negatively affect logistics costs and service quality. This study aims to develop a logistics-based approach to managing information flows in pharmacy chains. The research is based on system analysis, economic and statistical methods, and modeling techniques. The study analyzes the current state of the pharmaceutical retail market in Uzbekistan and identifies key problems in information support for pharmacy chains. As a result, an organizational model for information support of order management and a methodological approach to inventory optimization were proposed. The implementation of the proposed model contributes to reducing logistics costs, increasing inventory turnover, and improving coordination between pharmacies and distribution centers.